Baikal seal (Pusa sibirica Gmelin 1788, Phocidae). 1. Results of the experiment on heightened commercial withdrawal (retrospective evaluation) - E. A. Petrov (Известия ТИНРО)
Dynamics of the main parameters of the Baikal seal population (age and sex structure, size and weight indices, reproductive activity) in the years of experiment with heightened commercial withdrawal of the seals (1977–1985) is analyzed on the base of primary field data collected during the spring hunting. The problem of natural limitation for the population abundance is discussed for the case when further growth is limited by carrying capacity of the habitat. The observed changes of age, sex, size, and reproductive parameters reflected intrapopulation processes of the abundance regulation, weakly associated with trophic and density factors. Despite intensive commercial load and negative consequences of unusually early ice melting in 1981, the number of Baikal seal grew until the late 1980s. The withdrawal did not lead to expected improvement of the population status that was explained by underestimation of the stock. Low level (or complete absence) of biological substantiation for the experiment is noted.